Civic and political engagement among young adults in Ireland - James Laurence; Emer Smyth (The Economic and Social Research Institute (ESRI), 2023)
International research has shown that civic engagement, that is, volunteering in local services, can benefit both young people and their communities, while political engagement can strengthen a society's democratic culture. The Better Outcomes, Brighter Futures (2019) policy framework highlights the importance of young people feeling connected, respected and contributing to their world. To date, however, there has been an absence of systematic research on this aspect of young people's transition to adulthood in Ireland. Further, although the government strategy Our Rural Future highlights a lack of access to facilities and transport for young people living in rural areas, little is known about how this might impact on their civic and political engagement. It is therefore crucial to have an evidence base to identify the drivers of civic engagement in order to better support young people's involvement. This study aims to fill this gap by drawing on rich information on 20 year olds from Cohort '98 of the Growing Up in Ireland (GUI) study.
Keywords: 330; Ehrenamtliche Arbeit; Politische Partizipation; Jugendliche; Irland